Parents And Jobs Of Parents With Student Achievements - Ferdiansyah Agung Saputra; Safruddin; Edison Siringoringo (Comprehensive Health Care, 2019)
According to the World Health Organization (WHO) in 2015 had 42 million children who were overweight. This figure rose to 31 million from 2000. Obesity adolescents tend to have an impact on learning achievement and their health. The purpose of this study was students in senior high school 3 Bulukumba. 265 respondents sampling technique used consecutive sampling technique this type of research is an analytical study with a cross-sectional approach. The test used for the relationship of obesity whit student achievement is the fisher’s exact test while the test used for the relationship of parental work with student achievement is the Kolmogorov Smirnov test. The results of the study are respondents with type 1 obesity with good achievement scores of 27 respondents (87.1%) and achievement scores of less than 4 respondents (12.9%). While respondents with type 2 obesity with good performance scores were 9 respondents (56.2%) and achievement scores were less than 7 respondents. And the work of parents as PNS with a good achievement value of 15 respondents (93.8%) and less achievement scores of 1 respondent (1.6%). While respondents with the work of parents as entrepreneurs with good achievement scores of 10 respondents (55.6%) and achievement scores of less than 8 respondents (44.4%). Then the work of parents as farmers with good performance scores as many as 11 respondents. While the achievement score is less than 2 respondents (3.8%). The conclusion of this study is there's is a relationship of obesity with the achievement of students in senior high school 3 Bulukumba between parental work and the achievement of students in high school 3 Bulukumba. As for the suggestion in this study can add library references and student insights on Sitekes Panrita Husada Bulukumba.